Negara tanpa hukum : catatan pengacara jalanan - Alkostar, Artidjo (Yogyakarta, [Indonesia]: Pustaka Pelajar, 2000)
Law enforcement and violations of human rights in Indonesia.
Includes bibliographical references (p. 405-414).
Keywords: Human rights -- Indonesia; Law and politics -- Indonesia; Democratization; Indonesia -- Politics and government -- 1998-